Education and learning in the early Islamic world - Gilliot, Claude (The formation of the classical Islamic world, 2012)
Presents studies that are arranged under five headings: the pedagogical tradition; scholarship and attestation; orality and literacy; authorship and transmission; and libraries. This work presents a picture of the beginnings and evolution of education and learning in the Islamic world